The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1103/physreva.100.023416
|View full text |Cite
|
Sign up to set email alerts
|

Voigt-effect-based three-dimensional vector magnetometer

Abstract: We describe a method to dispersively detect all three vector components of an external magnetic field using alkali atoms based on the Voigt effect. Our method relies on measuring the linear birefringence of the radio frequency dressed atomic medium via polarization homodyning. This gives rise to modulated polarization signals at the first and second harmonic of the dressing frequency. The vector components of the external magnetic field are mapped onto the quadratures of these harmonics. We find that our schem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…(2)] and can be solved by employing the Floquet expansion. This solution predicts sensitivity to all three vector components of the magnetic field as reported in the experimental work in [22]. This FIG.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…(2)] and can be solved by employing the Floquet expansion. This solution predicts sensitivity to all three vector components of the magnetic field as reported in the experimental work in [22]. This FIG.…”
Section: Introductionsupporting
confidence: 64%
“…On the other hand, in Ref. [22] we have shown that indeed it is possible to employ dispersive measurements based on Voigt rotation when working with aligned states driven by radio-frequency fields, also showing vector magnetometry operation (see Fig. 2).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations